Spatial Modeling of Forest Cover Change in Kubu Raya Regency, West Kalimantan - Hanifah Ikhsani; I Nengah Surati Jaya; Muhammad Buce Saleh (Jurnal Manajemen Hutan Tropika, 2018)
Forest cover change is one of the environmental issues that continually gotten an international attention. This study describes how to develop a spatial model of forest cover change in each village-based typology by considering various bio-physical and social-economic factors. The village typologies were investigated by applying the clustering analysis approach. The objective of this study was to develop the spatial model and to identify the driving forces of forest cover change by village in Kubu Raya Regency of West Kalimantan. Based on proportion of forest in 2015, the study found that there are two village typologies within the study area with 81% overall accuracy (OA). The typology 1 (T1) which has low forest cover change rate of 5001.8 Ha per year consisted of 56 villages, while the typology 2 (T2) which has high rate of forest cover change of about 8050.6 Ha per year covered 34 villages. The study also recognized that the most significant driving forces of forest cover change in T1 were distance from rivers (X2) and settlements (X3), whereas in T2 were distance from roads (X1) and the edge of forest in 2015 (X9). The best spatial model of forest cover change are Y = -0.01+0.0001X2+0.0004X3 with OA of 83% and mean deviation (SR) 10.5% for T1 and Y = 0.02+0.0001X1-0.0002X9with OA 53% and SR 13.3% for T2. The study concludes that the proximity from the center of the human activities hold a significant influence to the behavior of forest cover changes